Effect of hot carcass weight on the rate of temperature decline of pork hams and loins in a blast-chilled commercial abattoir() - Overholt, Martin F (J Anim Sci, 2019)
Adequate carcass chilling is required to optimize pork quality and food safety. The rate at which carcasses chill is dependent on their mass. Hot carcass weight has increased steadily over the years, certainly affecting the chilling rate of the average carcass in contemporary abattoirs. Therefore, the objective was to model the effect of HCW on temperature decline of a contemporary population of pork carcasses slaughtered at a commercial abattoir that used a blast-chilling method. In addition, carcasses were sorted into HCW classes, and the effect of HCW group was tested on the rate of temperature decline of the longissimus dorsi and semimembranosus. Hot carcass weight, internal temperature of the loin muscle (at the 10th rib) and ham, as well as ambient temperature, were recorded from 40 to 1,320 min postmortem (45 time points) on 754 pork carcasses. An exponential decay model based on Newton’s law of cooling, [Formula: see text] , was fit to temperature decline of the ham and loin of the whole population using PROC MODEL of SAS. The initial models for the decline of both ham and loin temperature displayed significant autocorrelation of errors based on evaluation of the autocorrelation function plots and Durbin–Watson test (P < 0.0001). Therefore, second- and third-order autocorrelation parameters were tested. Based on Durbin–Watson test, the use of second-order autocorrelation model with lags of 1 and 2 was deemed adequate and was therefore included in all subsequent models. This base model and its respective parameter estimates were all significant (P < 0.01) for the whole population. Carcasses approximating 85, 90, 95, 100, and 105 kg (± 1 kg) were selected and binned into their respective weight classes. Dummy variables were used to compare the effect of HCW class on parameter estimate of ham and loin models. The developed model significantly fit all weight classes (P < 0.01) for both ham and loin temperature decline. For both loin and ham models, estimates of the rate constant (k) generally decreased as HCW increased. For loin temperature, k estimate for 105-kg carcasses was 0.00124 less (P = 0.02) than 85-kg carcasses, with the intermediate HCW classes not differing from the 85-kg class. For ham temperature, estimates of k for 90, 95, 100, and 105 kg HCW were all significantly and successively less than the k estimate for 85 kg class. For perspective, loins of 95-kg carcasses were estimated to reach 2 °C in 17 h, whereas loins from 105-kg carcasses would not reach 2 °C until 27 h. For hams, 95-kg carcasses were projected to reach 2 °C in 21 h, whereas those from 105-kg carcasses would take 28 h. Overall, HCW significantly affects the rate of temperature decline of pork hams, but not loins from pork carcasses weighing between 85 and 100 kg.